Niche partitioning among dead wood-dependent beetles - Horák, Jakub (Scientific reports, 2021)
Niche partitioning among species with virtually the same requirements is a fundamental concept in ecology. Nevertheless, some authors suggest that niches have little involvement in structuring communities. This study was done in the Pardubice Region (Czech Republic) on saproxylic beetles with morphologically similar larvae and very specific requirements, which are related to their obligatory dependence on dead wood material: Cucujus cinnaberinus, Pyrochroa coccinea, and Schizotus pectinicornis. This work was performed on 232 dead wood pieces at the landscape scale over six years. Based on the factors studied, the relationships among these species indicated that their co-occurrence based on species presence and absence was low, which indicated niche partitioning. However, based on analyses of habitat requirements and species composition using observed species abundances, there was no strong evidence for niche partitioning at either studied habitat levels, the tree and the microhabitat. The most likely reasons for the lack of strong niche partitioning were that dead wood is a rich resource and co-occurrence of saproxylic community was not driven by resource competition. This might be consistent with the theory that biodiversity could be controlled by the neutral drift of species abundance. Nevertheless, niche partitioning could be ongoing, meaning that the expanding C. cinnaberinus may have an advantage over the pyrochroids and could dominate in the long term.
Keywords: Animals; Forests; biodiverzita; Coleoptera; lesy; druhová specificita; brouci; Species Specificity; stromy; Czech Republic; dřevo; Wood; Biodiversity; ekosystém; Česká republika; Ecosystem; Larva; zvířata; Trees; larva